Citra Perempuan dalam Novel Metropop “Tetralogi Empat Musim” Karya Ilana Tan - Tania Intan; Vincentia Tri Handayani; Witakania Sundasari Som (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
When the storyline of chick lit and teen lit is always dominated by female figures, the metropop shows female and male figures. However, like popular novels that are more read and written by women, the metropop always presents issues that are centered on women. Therefore, this research was conducted with the aim of revealing the image of women in the ‘Tetralogi Empat Musim’ metropop by Ilana Tan consisting of ‘Summer in Seoul’ (2006), ‘Autumn in Paris’ (2007), ‘Winter in Tokyo’ (2008), and ‘Spring in London’ (2010). Data was collected by note-taking technique, and analyzed by descriptive-qualitative method. The methodological approach and the theoretical basis adopted for this research are feminist literary criticism. The results of the analyse indicate that in the tetralogy, (1) female self-image is displayed subject with TWITS (Teenage Women in Their 30s) characteristics, namely single, independent, working, aged between 24-30 years, beautiful and attractive, living in urban areas, lifestyle metropolis, heterosexual, and have character ‘The Waif’, and have 'weakness'. (2) The social image of women is described as being still the object of a patriarchal system in the form of dependence on male figures due to love relationships.